PROOF OF THE CRIME OF SEXUAL VIOLENCE AFTER THE PASSAGE OF THE SEXUAL VIOLENCE LAW - Nurafni Faradillah; Farida Patittingi; Ratnawati (Awang Long Law Review, 2023)
This study aims to analyze the proof of the crime of sexual violence after the legalization of the criminal act of sexual violence and what are the inhibiting factors in proving the crime of sexual violence after the legalization of the criminal act of sexual violence. The type of research that researchers use is normative-empirical legal research. This research was conducted in Makassar City, namely at the Makassar Polrestabes, Makassar District Court, LBH APIK Sulsel, UPTD PPA Makassar, and the Makassar University Sexual Violence Task Force. The results obtained through library research and interviews were then analyzed using qualitative analysis methods with a normative-empirical approach. The results of the study show that: 1) Law enforcers, both at the Police and the Attorney General's Office, do not fully understand the substance of the law on the crime of sexual violence, especially with regard to evidence, especially regarding the witness statement which does not absolutely have to be two, but only one witness statement plus other evidence is sufficient. as well as the judge's belief that sexual violence has occurred, so that law enforcers have not fully implemented the law on the crime of sexual violence.